The great dictionary caper - Sierra, Judy; Comstock, Eric (New York : Simon & Schuster Books for Young Readers, 2018)
When the words in the dictionary get bored and leave to attend a convention in Hollyword, it is up to Noah Webster to restore (alphabetical) order.
School Library Journal, December 2017
Booklist starred, December 2017
Pub Weekly, October 2017
Kirkus starred, November 2017
3.3.
K-3.
Keywords: Webster, Noah, -- 1758-1843 -- Juvenile fiction; Encyclopedias and dictionaries -- Juvenile fiction; Vocabulary -- Juvenile fiction; Webster, Noah, -- 1758-1843 -- Fiction; Encyclopedias and dictionaries -- Fiction; Vocabulary -- Fiction; Humorous fiction; Word games -- Fiction